Recent Developments in Chemical Synthesis with Biocatalysts in Ionic Liquids - Potdar, Mahesh K. (Molecules, 2015)
Over the past decade, a variety of ionic liquids have emerged as greener solvents for use in the chemical manufacturing industries. Their unique properties have attracted the interest of chemists worldwide to employ them as replacement for conventional solvents in a diverse range of chemical transformations including biotransformations. Biocatalysts are often regarded as green catalysts compared to conventional chemical catalysts in organic synthesis owing to their properties of low toxicity, biodegradability, excellent selectivity and good catalytic performance under mild reaction conditions. Similarly, a selected number of specific ionic liquids can be considered as greener solvents superior to organic solvents owing to their negligible vapor pressure, low flammability, low toxicity and ability to dissolve a wide range of organic and biological substances, including proteins. A combination of biocatalysts and ionic liquids thus appears to be a logical and promising opportunity for industrial use as an alternative to conventional organic chemistry processes employing organic solvents. This article provides an overview of recent developments in this field with special emphasis on the application of more sustainable enzyme-catalyzed reactions and separation processes employing ionic liquids, driven by advances in fundamental knowledge, process optimization and industrial deployment.